2019
DOI: 10.3390/nu11112732
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Vitamin D Specific Questionnaire to Determine Vitamin D Status in Athletes

Abstract: The study objective was to validate a food frequency and lifestyle questionnaire (FFLQ) to assess vitamin D intake and lifestyle factors affecting status. Methods: Data collected previously during the fall (n = 86), winter (n = 49), and spring (n = 67) in collegiate-athletes (Study 1) and in active adults (n = 123) (Study 2) were utilized. Study 1: Vitamin D intake and ultraviolet B exposure were estimated using the FFLQ and compared to serum 25(OH)D concentrations via simple correlation and linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…It has been shown that male and female athletes that train indoors during the fall and winter months suffer from low vitamin D levels [ 40 ]. Since vitamin D is only found in limited natural and fortified foods such as fatty fish, mushrooms, egg yolks, and cereals, it is unlikely that adequate vitamin D status can be maintained through food alone in the present athlete population [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that male and female athletes that train indoors during the fall and winter months suffer from low vitamin D levels [ 40 ]. Since vitamin D is only found in limited natural and fortified foods such as fatty fish, mushrooms, egg yolks, and cereals, it is unlikely that adequate vitamin D status can be maintained through food alone in the present athlete population [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) was calculated as weight divided by height in meters squared and body surface area (BSA) was calculated using the Mosteller equation [ 36 ]. Participants also completed a vitamin D-specific food frequency and lifestyle questionnaire (FFLQ) [ 37 ]. The FFLQ addresses questions about the frequency of consumption of vitamin D-containing foods, vitamin D supplementation, sun exposure and tanning bed usage.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, researchers observed a significant association of serum 25(OH)D with tanning bed use in the spring, supplement use in the fall, and BMI across all seasons. These results indicate the influence of factors—other than diet—on the serum concentrations of calcifediol [ 33 ]. Because the main dietary sources of vitamin D are of animal origin, a recent simulation study estimated the dietary shifts necessary to optimize vitamin D intake and minimize the carbon footprint.…”
Section: Vitamin D Sources and Metabolismmentioning
confidence: 99%